Is the information available on the Web influencing the way parents see ENT surgical procedures? - Nogueira Júnior,João Flávio (2009)
INTRODUCTION AND AIMS: the Internet is the world's fastest growing source of health related information. Parents and guardians are increasingly turning to the Internet for information about their children's medical conditions and treatments. This paper has the following objectives 1) determine the prevalence of web searches for medical information performed by parents/guardians of children undergoing ENT surgery in a private hospital of Sao Paulo, Brazil. 2) assess whether the gathered information influenced the parents/guardians' decision on the treatment/surgery. METHOD: questionnaire voluntarily responded by 132 parents/guardians of children submitted to ENT surgery in a private hospital in Sao Paulo, Brazil. CONCLUSIONS: 117 parents/guardians (90%) used the Internet to search for information on the disease and surgical treatment of the children. Only 12 parents/guardians (10%) discussed the information with the physician assigned to perform the surgical procedure. 91 parents/guardians (78%) said that the information had impact upon the decision to have surgery performed on their children.